Prevalence of intimate partner violence and reproductive health outcomes among Afghan refugee women in Iran. Issue 2 (1st February 2019) - Delkhosh, Marjan; Merghati Khoei, Effat; Ardalan, Ali; Rahimi Foroushani, Abbas; Gharavi, Mohammad Bagher
Abstract: Refugee women are at high risk of experiencing high level of Intimate Partner Violence (IPV) and its negative impacts. We conducted a cross-sectional population-based household survey with refugees in a settlement in the city of Semnan, Iran, from 2016 to 2017. Afghan refugee women ( n  = 188) with ages between 15 and 49 years were recruited for the survey. Overall, about 79.8% of the participants reported to have experienced a form of IPV in the past 12 months. IPV exposure is associated with a negative reproductive health outcome. The high prevalence of IPV found among refugee women in the present research and its strong links with poor reproductive health outcomes, underline the urgent need for the development and testing of appropriate interventions in refugee settlements.